2013
DOI: 10.1111/apm.12086
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of the role and relationship between Notch‐1 and Oct‐4 expression in urinary bladder carcinoma

Abstract: Most tumors contain a minor population of cancer stem cells that are responsible for tumor heterogeneity, resistance to therapy and recurrence. Oct-4 is a transcription factor responsible for self-renewal of stem cells, whereas the Notch family of receptors and ligands may play a pivotal role in the regulation of stem cell maintenance and differentiation. This study aimed at an evaluation of Oct-4 and Notch-1 expression in both carcinoma and stromal cells of 83 cases of primary bladder carcinoma and to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…NOTCH1 and DLL1 were most consistently diminished in both cell lines and tissues. Downregulation of these factors is in accord with a previous report [19], whereas another paper reported decreased NOTCH1 expression in high-grade invasive UC tissues only, with more pervasive cytoplasmic localization [28]. The mechanisms underlying these changes remain to be determined.…”
Section: Discussionsupporting
confidence: 87%
“…NOTCH1 and DLL1 were most consistently diminished in both cell lines and tissues. Downregulation of these factors is in accord with a previous report [19], whereas another paper reported decreased NOTCH1 expression in high-grade invasive UC tissues only, with more pervasive cytoplasmic localization [28]. The mechanisms underlying these changes remain to be determined.…”
Section: Discussionsupporting
confidence: 87%
“…The Notch signaling pathway performs crucial roles in maintaining cell fate/proliferation, regulating the stem cell maintenance and differentiation and epithelial–mesenchymal transition (EMT) [ 94 , 95 , 96 ]. GGI network analysis revealed some exciting functions of Notch factors in BCa, including stem cell development and cell fate determination, indicating peculiar roles for DTX1, DLL3, DLL1, JAG1, and JAG2 in terms of Notch binding, while others are not involved.…”
Section: Discussionmentioning
confidence: 99%
“…Abdou et al described the fact that NOTCH1 over-expression in stromal cell potentially activates Oct-4 (one of the crucial regulators of cell self-renewal) and is associated with poor prognosis and liability for recurrence in BCa [ 96 , 97 , 98 ]. Furthermore, loss-of-function mutations in NOTCH1 and NOTCH2 promote an epithelial–mesenchymal transition (EMT) in BCa, stabilizing the mesenchymal phenotype [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this, we performed Matrigel invasion chamber assays, and we observed increased invasion in shHES1-and siHES1-treated T24 cells compared with cells treated with a nontargeting control ( Figure 5D). have suggested that the NOTCH pathway could be oncogenic in bladder cancer (37,38), there is substantial evidence indicating a tumor-suppressive role. In particular, a high fraction of bladder carcinomas present deletion of the long arm of chromosome 9q, where NOTCH1 is located (39), and low levels of NOTCH1 and JAGGED1 are associated with short survival in bladder cancer patients (40).…”
Section: Discussionmentioning
confidence: 99%